Carbide decorated carbon nanotube electrocatalyst for high-efficiency hydrogen evolution from seawater. Issue 96 (29th September 2016) - Zhao, Yuanyuan; Tang, Qunwei; He, Benlin; Yang, Peizhi
Abstract : Co3 Mo3 C/CNT electrocatalysts are developed for high-efficiency hydrogen evolution by seawater splitting. Abstract : Pursuit of robust electrocatalysts has been a persistent objective for hydrogen evolution from seawater. We present here an experimental realization of an efficient Co3 Mo3 C decorated carbon nanotube (Co3 Mo3 C/CNT) electrocatalyst with exceptionally high electrocatalytic activity and good durability through a simple thermal decomposition method for hydrogen evolution reaction (HER), yielding an onset overpotential as low as 42 mV and an exchange current density up to 0.415 mA cm −2 in seawater. Notably, the resultant Co3 Mo3 C/CNT electrocatalyst displays a promising stability when suffering persistent operation over 26 h in seawater. In comparison with pristine Ni foam electrode, the Co3 Mo3 C/CNT can markedly reduce the overpotential for hydrogen evolution and therefore enhance HER kinetics.